2014
DOI: 10.1080/00288233.2014.961644
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen leaching losses from lysimeters containing winter kale: the effects of urinary N rate and DCD application

Abstract: Nitrogen (N) leached from the plant-soil system is an environmental concern. The objective of this study was to quantify N leaching losses from cow urine deposited during grazing of a winter forage crop (kale), and determine the effect of using the nitrification inhibitor dicyandiamide (DCD) to reduce N leaching losses. Fresh cow urine was applied to the surface of large soil monolith lysimeters in late June 2011 at two urinary N deposition rates; 500 and 700 kg N ha −1 (with and without DCD), and compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…Liu et al (2013) observed that the application of dicyandiamide and 3,4-dimethylpyrazol phosphate slightly decreased the soil N-NO3 -contents and significantly increased the soil N-NH4 + contents in the study. Malcolm et al (2015) state that, the application of dicyandiamide reduced N-NO3 -leaching losses by up to 54%. However, some previous studies have shown a shorter longevity and lower mobility of dicyandiamide compared with other nitrification inhibitors (Zerulla et al, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Liu et al (2013) observed that the application of dicyandiamide and 3,4-dimethylpyrazol phosphate slightly decreased the soil N-NO3 -contents and significantly increased the soil N-NH4 + contents in the study. Malcolm et al (2015) state that, the application of dicyandiamide reduced N-NO3 -leaching losses by up to 54%. However, some previous studies have shown a shorter longevity and lower mobility of dicyandiamide compared with other nitrification inhibitors (Zerulla et al, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Further, as a proportion of the amount of N applied to the lysimeters in the urine, an equivalent of 21%-32% was leached as NO 3 − -N. In the study of Malcolm et al (2014) where N leaching losses beneath winter kale were reported, there was a higher proportional leaching loss, equivalent to 43% and 54%, when urine was applied at the higher rates of 500 and 700 kg N ha −1 , respectively. This is similar to trends observed in grazed pasture systems (Cameron et al 2013), suggesting an exponential relationship between urine-N loading rate and N leaching losses under winter forage crop systems.…”
Section: Leaching Losses From Lysimetersmentioning
confidence: 99%
“…The soil surface inside the lysimeters was then heavily trampled using a manually operated trampling device as described in Malcolm et al (2014).…”
Section: Crop and Soil Managementmentioning
confidence: 99%
See 2 more Smart Citations